MANAGING POLYCHLORINATED BIPHENYLS IN COMPLIANCE WITH THE STOCKHOLM CONVENTION: BANGLADESH IN CONTEXT - KHAN, BAHREEN; HOSAIN, MD. MOSTAFA (Journal of Malaysian and Comparative Law, 2025)
The use of hazardous substances (HS), chemicals and hazardous waste (HW), invites multifaceted issues affecting the economy, society and natural environment. The findings of literature by authoritative scientific bodies confirm that the production and excessive use of HS and HW are deleteriously impacting the environment, ecosystems, human health, and wildlife. Due to their ability to persist in nature for long periods and cause harm, some of these chemicals are classified as persistent organic pollutants (POPs). Among these POPs, polychlorinated biphenyls (PCBs) are significant and have been used in various industrial and commercial products, mainly in electrical equipment. The environmentally sound management (ESM) of PCBs, other hazardous POPs, and their wastes is a pressing concern for all States regardless of their size and nature. Developing countries, in particular, have become victims of excessive use for various reasons. To address issues pertaining to POPs, the Stockholm Convention (StC) was adopted in 2001. Bangladesh, as a party to the StC, has taken various regulatory initiatives to control the release and ensure the ESM of POPs and various HS, chemicals and HW. This article assesses the extent to which and the effectiveness with which Bangladesh’s legal and policy instruments have integrated the obligations of the StC regarding the ESM of PCBs. The findings of this research have the potential to guide the stakeholders of Bangladesh in bringing necessary changes in its regulatory framework, and also for other developing countries in charting their future directions regarding PCBs management.